2017
DOI: 10.1007/s00167-017-4574-y
|View full text |Cite|
|
Sign up to set email alerts
|

Patient and surgical characteristics that affect revision risk in dynamic intraligamentary stabilization of the anterior cruciate ligament

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
67
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 36 publications
5
67
0
3
Order By: Relevance
“…15 Other studies have reported crude rates of approximately 4% for revision ACLR and 5% for contralateral ACLR at 5 years 1,12,22 and 3% for both procedures at 2-year follow-up. 13,24 The higher risk of revision and contralateral ACLR in male and young patients is a consistent finding in many studies 8,9,15,21,22,25 and may represent patients with an increased tendency to return to riskier sports (ie, rugby). Return to sport is associated with an increased risk of graft failure and contralateral ACLR, especially in high-level or high-risk pivoting and cutting sports.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…15 Other studies have reported crude rates of approximately 4% for revision ACLR and 5% for contralateral ACLR at 5 years 1,12,22 and 3% for both procedures at 2-year follow-up. 13,24 The higher risk of revision and contralateral ACLR in male and young patients is a consistent finding in many studies 8,9,15,21,22,25 and may represent patients with an increased tendency to return to riskier sports (ie, rugby). Return to sport is associated with an increased risk of graft failure and contralateral ACLR, especially in high-level or high-risk pivoting and cutting sports.…”
Section: Discussionsupporting
confidence: 53%
“…Return to sport is associated with an increased risk of graft failure and contralateral ACLR, especially in high-level or high-risk pivoting and cutting sports. 1,3,6,8,10,14,19,21,25 Male patients are known to be more likely to attempt to return to sport after ACLR, 4 and a study from the United States found that 92% of patients younger than 18 years returned to high-risk sports after ACLR compared with 68% in those older than 25 years. 22…”
Section: Discussionmentioning
confidence: 99%
“…21 Of note is that hardware removal did not appear to negatively influence knee laxity, and tibial bone loss after removal of the tibial implant did not seem to interfere with revision ACL surgery. 19,22,27 It is recommended that future research differentiate between hardware removal for medical and nonmedical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The reported revision rate in this cohort is lower than those of previously reported publications, which range between 4.8% and 9% [ 11 , 12 , 13 ]. These might be attributed to small sample sizes [ 8 ] or lower patients’ age [ 11 , 12 ], as Meister et al and Henle et al showed for dynamic intraligamentary stabilization (DIS) that younger patients tend to be more prone to a re-tear [ 20 , 21 ]. However, we were not able to identify age or pre-traumatic level of activity as a risk factor for a re-tear.…”
Section: Discussionmentioning
confidence: 99%